The mediator role of the feeling of personal unaccomplishment in the effect of unemployment anxiety on depression: a research on business faculty students in Türkiye - Yumusak, Ibrahim Güran (Frontiers in Public Health, 2024)
Background This study aims to determine how the unemployment anxiety of university students affects their depression level. It also examines the mediating role of the feeling of personal unaccomplishment between these effects. Methods The data was analyzed using the PROCESS method. The research was conducted on 843 students attending different public or foundation (private) universities in Türkiye. Random sampling was used to select the participants. Results As a result of the analysis, it was determined that there is a positive, significant, moderate (R = 0.509, p < 0.01) relationship between unemployment anxiety and depression and a positive, significant and weak relationship between unemployment anxiety and feeling of personal unaccomplishment (R = 0.102, p < 0.01), there is a positive, significant, and weak (R = 0.184, p < 0.01) relationship between feeling of personal unaccomplishment and depression. Unemployment anxiety of university students had significant and positive effects on their depression level and significant and positive effects on feelings of personal unaccomplishment of students. Conclusion As a result of the mediating variable analysis, it was determined that the feeling of personal unaccomplishment has a partial mediator role in the relationship between unemployment anxiety and depression.